2018
DOI: 10.1002/jsde.12003
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of Anionic Sulfonate Gemini Surfactants and Their Interactions With Anionic Polyacrylamide

Abstract: Anionic sulfonate gemini surfactants 8-s-8 (SO 3 ) 2 and 12-s-12(SO 3 ) 2 (s = 3, 6) were synthesized, and their micellization in aqueous solution at 25.0 C and pH 9 was investigated. The results show that the critical micelle concentrations (CMC) of 8-s-8(SO 3 ) 2 are more than 2 orders of magnitude larger than those of 12-s-12(SO 3 ) 2 , but the spacer length has a relatively small impact on the CMC. Moreover, the interactions of n-s-n(SO 3 ) 2 (n = 8, 12; s = 3, 6) with anionic polyacrylamide (PAM) at 25.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This makes the solution low in viscosity under high shear, easy to pump, and re-forms the network structure at a low flow rate deep in the formation and restores viscoelasticity (Chakraborty et al, 2011;Yu et al, 2014). Also, Gemini surfactants can achieve ultra-low interfacial tension at a lower concentration, which can effectively reduce oil-water interfacial tension, which makes Gemini surfactants have significant advantages in expanding swept volume and improving oil displacement efficiency (Jianxi, 1999;Li et al, 2016a;Wang et al, 2018;Zhao, 2014). From the structure and performance characteristics of Gemini surfactants, it is more in line with our requirements for viscoelastic surfactants for oil displacement.…”
Section: Current Problems and Solutions Of Viscoelastic Surfactant Floodingmentioning
confidence: 99%
“…This makes the solution low in viscosity under high shear, easy to pump, and re-forms the network structure at a low flow rate deep in the formation and restores viscoelasticity (Chakraborty et al, 2011;Yu et al, 2014). Also, Gemini surfactants can achieve ultra-low interfacial tension at a lower concentration, which can effectively reduce oil-water interfacial tension, which makes Gemini surfactants have significant advantages in expanding swept volume and improving oil displacement efficiency (Jianxi, 1999;Li et al, 2016a;Wang et al, 2018;Zhao, 2014). From the structure and performance characteristics of Gemini surfactants, it is more in line with our requirements for viscoelastic surfactants for oil displacement.…”
Section: Current Problems and Solutions Of Viscoelastic Surfactant Floodingmentioning
confidence: 99%
“…However the ratio shifts to the right with the increase in number of carbons in the hydrophobic block for the 6,12-ionene [137]. Wang et al showed that increasing the alkyl chain groups from 8 to 12 carbon for a Gemini surfactant significantly increased the viscosity, with a significant jump between the CAC and CMC, where the shorter alkyl chain Gemini surfactant steadily increased in viscosity with surfactant concentration during the entire regime [138].…”
Section: Outcomes Of Complexation-rheologymentioning
confidence: 99%
“…For example, Molnar and Reiger studied the interaction between polyelectrolyte chains in the presence of calcium ions, Schweins et al studied the calcium ion-mediated conformational changes in polyelectrolyte chains, and Hsiao and Luijten studied the effect of calcium ion concentration on the collapse–expansion transition in polyelectrolytes . The interaction between like-charged polyelectrolytes and surfactants , has received lesser attention than that between oppositely charged or neutral polyelectrolytes and surfactants. In our previous work, we discussed the possibility of achieving the desired response of PSS-Ca binding to the presence of the anionic surfactant dodecyl sulfate (DS). Additionally, we also investigated the effect of tacticity and the degree of sulfonation on the above response .…”
Section: Introductionmentioning
confidence: 99%